2015
DOI: 10.5901/mjss.2015.v6n4s3p647
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Stress and Job Satisfaction: An Evidence from Malaysian Peacekeeping Mission

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
3
7
1
2
Order By: Relevance
“…Also, there was a relationship between stress and job satisfaction which was minimal. This finding is not in line with the report of Ismail, Ghani, Subhan, Joarder, and Ridzuan (2015) who deduced that physiological and psychological stresses have been recognized as important determinants of job satisfaction. Though the study showed the personnel were stressed to some extent, but that may not influence or relates to the job satisfaction.…”
Section: Discussioncontrasting
confidence: 98%
“…Also, there was a relationship between stress and job satisfaction which was minimal. This finding is not in line with the report of Ismail, Ghani, Subhan, Joarder, and Ridzuan (2015) who deduced that physiological and psychological stresses have been recognized as important determinants of job satisfaction. Though the study showed the personnel were stressed to some extent, but that may not influence or relates to the job satisfaction.…”
Section: Discussioncontrasting
confidence: 98%
“…Moreover, those dissatis ed with their job are highly stressed compared to those who are satis ed. To substantiate our study ndings, Dagget et al 6 and others 50,51,52,53 found job satisfaction as a predictor for WRS among nurses. However, Gulavani 39 has reported dissimilar ndings whereas job satisfaction was not related to occupational stress.…”
Section: Discussionsupporting
confidence: 89%
“…This happens allegedly because of the benefit package received by the employees which compensate their stress. Other finding from Gyamfi even further, argued that role ambiguity which could cause work stress did not have significant effect on job satisfaction [49]. Despite various result we support the majority of the studies which show negative relationships.…”
Section: Resultssupporting
confidence: 41%